Key Success Factors of Organizational Success: A Study of MULA Car International - Muhammad Ashraff; Daisy Mui Hung Kee; Roshini A/P Subramaniam; Nur Hazimah; Nur Aina Syafiqah (AIBPM Publisher, 2020)
This study is conducted to examine how does MULA Car International deal with organizational behavioural issues in the company to meet the objectives and goal of their e-hailing service business. MULA is an e-hailing business that uses “Internet Plus Transportation” model in the traffic service market. The study began with gathering information about obstacles and barriers that challenge MULA while operating towards their goal. In the study, it shows that employees are the main drivers for their success and development in the industry. We identified that MULA has come up with many impressive initiatives not only to attract more customers but also to satisfy their employees so that organizational commitment is developed. The purpose of this study is also to examine how MULA faces challenges in the company and use it as factors to develop the business and to remain competitive in the e-hailing industry.